2018
DOI: 10.1002/pros.23643
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐6 induces VEGF secretion from prostate cancer cells in a manner independent of androgen receptor activation

Abstract: Our results suggest that IL-6 might induce VEGF secretion from PCa cells in a manner independent of AR activation. To prevent IL-6-induced VEGF secretion, inhibition of the PI3K/AKT signaling pathway could be an important pharmacological goal regardless of ADT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…At the time of PSA progression, relative elevations (as compared with the 3‐month time point) were noted in IL‐6, VEGF, and IL‐27. These data are consistent with copious literature implicating IL‐6 as a pro‐inflammatory driver of PCa progression . However, these data show an association and do not prove causality.…”
Section: Discussionsupporting
confidence: 85%
“…At the time of PSA progression, relative elevations (as compared with the 3‐month time point) were noted in IL‐6, VEGF, and IL‐27. These data are consistent with copious literature implicating IL‐6 as a pro‐inflammatory driver of PCa progression . However, these data show an association and do not prove causality.…”
Section: Discussionsupporting
confidence: 85%
“…With respect to its requirement for cell viability and growth, most tellingly, one group studying astrocytes (Quintana et al, 2013;Quintana et al, 2008) found that while global IL-6R knockout (which leads to compensations) had a small effect, conditional knockout in astrocytes led to their apoptosis. In support of the involvement of IL-6R in cell growth, other papers have linked IL-6 to intestinal epithelial cell and fibroblast growth, VEGF-A secretion from prostate cancer cells (Ishii et al, 2018), bone metastases in breast cancer (Wakabayashi et al, 2018) and hepatocyte proliferation. Additionally, IL-6R has been linked to increased gp130 expression and upregulation of leukemia inhibitory factor (LIF), an alternative gp-130 signaling system able to compensate for IL-6R deficiency Liu et al, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…IL-6, which is produced by both PCa and stromal cells, is another fundamental player within the PCa microenvironment that influences many aspects of prostate tumorigenesis, including proliferation, angiogenesis, and insensitivity to androgens [40,125,126]. For example, CAF-secreted IL-6 induces VEGF secretion from PCa cells, stimulating tumor angiogenesis ( Figure 1) [40]. Due to its multiple effects on prostate TME, the clinical use of inhibitors of IL-6 or its related transcription factor STAT3 is under investigation [126].…”
Section: Caf-tumor Signaling: Paracrine Systemic Cell-cell Direct mentioning
confidence: 99%
“…Several studies indicate that CAFs also actively promote PCa resistance to anti-androgen therapies, thus inducing CRPC. CAF-derived IL-6 is involved in this process, with evidence suggesting that it could enable AR transcriptional activity in PCa cells in the absence of androgens by modulating MAPK, STAT3, and PI3K/AKT signaling [40,125]. In 3D co-culture models of CAFs/PCa cell lines, CAFs decrease the sensitivity to the anti-androgens bicalutamide and enzalutamide in a PI3K/Akt signaling-dependent manner [14].…”
Section: Caf-mediated Resistance To Androgen Deprivation and Chemothementioning
confidence: 99%